Analysis of pyrethroids in cereals by HPLC with a deep eutectic solvent-based dispersive liquid–liquid microextraction with solidification of floating organic droplets. Issue 5 (25th January 2021) - Wu, Beiqi; Guo, Zhengyan; Li, Xiuting; Huang, Xin; Teng, Chao; Chen, Zhenjia; Jing, Xu; Zhao, Wenting
Abstract : A hydrophobic deep eutectic solvent is used as a green extractant. Abstract : This work presents a novel and green analytical procedure involving a deep eutectic solvent-based dispersive liquid–liquid microextraction with solidification of floating organic droplets (DES-DLLME-SFOD) followed by HPLC to measure three pyrethroids (bifenthrin, β-cypermethrin, and deltamethrin) in cereal samples. Firstly, a low-density hydrophobic DES was synthesized from thymol and octanoic acid in the molar ratio of 1/4 and this was applied as a green extraction solvent in the DLLME procedure to avoid the use of a toxic extractant. After centrifugation and placing it on an ice bath, it is transformed into a solid phase on the top of the sample solution to reduce the loss of extractant, conducive to convenient collection thereafter. This procedure required the optimal conditions (including the type, proportion, and amount of DES as the extractant, the volume of the dispersant acetonitrile, the amount of salt, and the pH value) to be evaluated. Under optimized variates, the proposed method provided good linearity with a correlation coefficient greater than 0.997 and limits of quantification within the range of 6.6–8.9 μg kg −1 . The recoveries of pyrethroids in corn, wheat, barley, and oats were 75.6–87.2%, and the relative standard deviation was less than 3.6%. The method, therefore, offers a green, efficient, and convenient approach for the determination of pesticides in cereals.